Chest compression first aid for respiratory arrest due to acute asphyxic asthma. Issue 1 (22nd December 2009) - Harrison, R
Abstract : This report demonstrates the importance of including external chest compression as a method of resuscitation in first aid for cases of life-threatening asphyxic asthma. Chest compression may be the only way that death of such patients may be avoided. Three such patients, two with respiratory arrest, were successfully treated by external chest compression. During the 1960s, there was an increase in asthma deaths, 81% of which occurred unexpectedly, outside the hospital. This coincided with the abandonment of the trusted methods of chest compression and the introduction of mouth-to-mouth resuscitation. Acute asphyxic asthma was the most common cause of death. In acute asphyxic asthma, the chest wall does not deflate spontaneously. The trapped air must be expelled by external compression. Mouth-to-mouth resuscitation may not work because air is being blown in while none escapes.